Antireflux Metal Stent for Initial Treatment of Malignant Distal Biliary Obstruction - Shinichi Morita; Yasuaki Arai; Shunsuke Sugawara; Miyuki Sone; Yasunari Sakamoto; Takuji Okusaka; Shigetaka Yoshinaga; Yutaka Saito; Shuji Terai (Gastroenterology Research and Practice)
Objectives. To compare the use of an antireflux metal stent (ARMS) with that of a conventional covered self-expandable metal stent (c-CSEMS) for initial stenting of malignant distal biliary obstruction (MDBO). Materials and Methods. We retrospectively investigated 59 consecutive patients with unresectable MDBO undergoing initial endoscopic biliary drainage. ARMS was used in 32 patients and c-CSEMS in 27. Technical success, functional success, complications, causes of recurrent biliary obstruction (RBO), time to RBO (TRBO), and reintervention were compared between the groups. Results. Stent placement was technically successful in all patients. There were no significant intergroup differences in functional success (ARMS [96.9%] versus c-CSEMS [96.2%]), complications (6.2 versus 7.4%), and RBO (48.4 versus 42.3%). Food impaction was significantly less frequent for ARMS than for c-CSEMS (P=0.037), but TRBO did not differ significantly between the groups (log-rank test, P=0.967). The median TRBO was 180.0 [interquartile range (IQR), 114.0–349.0] days for ARMS and 137.0 [IQR, 87.0–442.0] days for c-CSEMS. In both groups, reintervention for RBO was successfully completed in all patients thus treated. Conclusion. ARMS offers no advantage for initial stent placement, but food impaction is significantly prevented by the antireflux valve.